The teaching of the History of Medicine in Italy: a path in progress - Siri, Anna; Gazzaniga, Valentina; Licata, Marta; Ciliberti, Rosagemma (Acta Biomedica Atenei Parmensis, 2021)
Background: The increasing attention to the potential application of technology in medicine represents a dangerous warning in the direction of a reductionist approach.The academic system should therefore be strongly engaged to ensure even in medical practice the greatest enhancement of the human dimension.Targets: How much space is offered to the teaching of History of Medicine (HM) in Italian Universities? This work aims to answer this question through an in-depth analysis of the teaching plans of the degree courses in Medicine and Surgery (CLMC) activated in Italy.Materials and Methods: The survey was carried out through the consultation of information, relating to the year 2019-2020, contained in the UniversItaly portal of the Italian Ministry of Education, University and Research, created to accompany students in their studies, as well as through the information published in the web portals of the various universities.Results and Discussion: In Italy in 43 out of 97 Universities there is the Degree Course in Medicine and Surgery for a total of 66 degree courses; some Universities have activated more degree courses depending on the number of learners or on issues of territorial distribution. The teaching of HM is present in the curricula of 54 CLMC (82%) and in these is mandatory. In 93% of the cases, it is included in integrated courses (CI) and for only 4 CLMC it results as autonomous teaching. For the most part (86%) it is included in the first year's educational plan. The typology of the different CIs is extremely varied, both in terms of denomination, year and content, as well as in the overall CFUs assigned. The current teaching staff is divided as follows: 6 full professors; 12 associate professors; 13 Researchers (RU/RD); 20 contract professors. 19 are the researchers/professors engaged in the scientific field of the HM (MED/02).Conclusion: Those findings indicate that the HM subject in the Italian medical education programs is not yet universally recognized as able to stimulate medical students to a holistic view of the person and illness and therefore not sufficiently valued.